Step
*
2
1
1
of Lemma
remove-repeats-length-one
1. T : Type
2. eq : EqDecider(T)
3. L : T List
4. x1 : T
5. (x1 ∈ L)
6. ∀y:T. y = x1 ∈ T supposing (y ∈ L)
7. set-equal(T;remove-repeats(eq;L);L)
8. x : T
9. y : T
10. (x ∈ remove-repeats(eq;L))
11. (y ∈ remove-repeats(eq;L))
⊢ x = y ∈ T
BY
{ ((Assert x = x1 ∈ T BY Auto) THEN (Assert y = x1 ∈ T BY Auto) THEN Auto)⋅ }
Latex:
Latex:
1.  T  :  Type
2.  eq  :  EqDecider(T)
3.  L  :  T  List
4.  x1  :  T
5.  (x1  \mmember{}  L)
6.  \mforall{}y:T.  y  =  x1  supposing  (y  \mmember{}  L)
7.  set-equal(T;remove-repeats(eq;L);L)
8.  x  :  T
9.  y  :  T
10.  (x  \mmember{}  remove-repeats(eq;L))
11.  (y  \mmember{}  remove-repeats(eq;L))
\mvdash{}  x  =  y
By
Latex:
((Assert  x  =  x1  BY  Auto)  THEN  (Assert  y  =  x1  BY  Auto)  THEN  Auto)\mcdot{}
Home
Index